Answer:
d
Step-by-step explanation:
The triangles are similar, thus the ratios of corresponding sides are equal, that is
= = ( cross- multiply )
5(2x + 1) = 8(x + 4) ← distribute parenthesis on both sides )
10x + 5 = 8x + 32 ( subtract 8x from both sides )
2x + 5 = 32 ( subtract 5 from both sides )
2x = 27 ( divide both sides by 2 )
x = 13.5 → d
Vcone=(1/3)hpir^2
base=diameter=2rdaius=6
diameter/2=3=radius
height=9.2
Vcone=(1/3)(9.2)pi(3^2)
Vcone=9.2pi3
vcone=27.6pi cm^3
aprox pi=3.141592
vcone=86.707 cm^3
round
86.7 cm^3
Answer:
2. is y=1.2x+6. 4. is y=2x+10
Step-by-step explanation:
The value of x that will make both equations to be equivalent to each other is = -56
From the equation:
0.75(x + 20) = 2 + 0.5(x - 2)
Open brackets
0.75x + 15 = 2 + 0.5x - 1
Collect like terms
0.75x - 0.5x = 2 - 1 - 15
0.25x = - 14
Divide both sides by 0.25
x = -56
Therefore, we can conclude that the value of x that will make both equations to be equivalent to each other is -56
Learn more about solving algebraic equations here:
0.75(x+20)=2+0.5(x-2)
Distribute on both sides
0.75x+15= 2+0.5x-1
Add common factors
0.75x+15=1+0.5x
Subtract 0.5x on both sides
0.25x+15=1
Subtract 15 on both sides
0.25x=-14
Divide by 0.25 on both sides
x = -56
(6y + 8)(y - 6)
6(y + 8)(y - 1)
6(y - 1)(y - 7)
Answer:
6 (y + 8) (y - 1)
Step-by-step explanation:
Factor the following:
6 y^2 + 42 y - 48
Factor 6 out of 6 y^2 + 42 y - 48:
6 (y^2 + 7 y - 8)
The factors of -8 that sum to 7 are 8 and -1. So, y^2 + 7 y - 8 = (y + 8) (y - 1):
Answer: 6 (y + 8) (y - 1)
PS: it's really helpful to pose the question correctly 6 y^2 + 42 y - 48 NOT
6y 2 - 48 + 42y
Answer:
6 (y + 8) (y - 1)
Step-by-step explanation: